(untitled) (Journal of Forestry, 2024)
An essential challenge in any environmental field (forestry, agriculture, etc.), which places an emphasis on data analysis for the purpose of decision making and problem solving, is the estimation of a dependent environmental variable (Y) through an independent one (X). In this work, a Microsoft Excel template is proposed for assessing a set of eleven popular regression Y-X models. Any researcher can use LineFit.xls as a modeling tool for assessing these eleven regression models and selecting the one that best fits their data by running tests on all regression assumptions and comparing models using the most common fitting comparison criteria. Microsoft Excel, being a widely used and user-friendly program, makes it easy to update, expand, and personalize the tests to meet specific needs.